Malaysian Adolescents And The (Re)Construction Of Identities On The Net. - Tan, Kok Eng (2006)
Malaysian adolescents, especially those living in urban areas, engage in various forms of writing in English that include the school essay, SMS phone texting, online chat, blogs, notes and poems.